STUDY OF TECHNOLOGICAL PROPERTIES OF A SEPARATION OBJECT AND FUNCTIONALITY OF THE WORKING BODIES OF SEPARATING EQUIPMENT - Ткаченко, Р. Н. (Scientific Progress & Innovations, 2015)
The work is devoted to the study of the movement of inoculum under the action of gravity in sowing system, namely metering system – sow automated – dialects device – undertenon space dovetail ploughshare – switchgear. The impact resistance when the flow of inoculum on the example of winter wheat was theoretically described. Which is considered with regard to the form of the profile of its convenient shape flow in sow automate, provided mechanical feeder that is able to asume and theoretically describe the general scheme of the movement of seed in sowing system.